Power of Articulation Imagery of Social Structure and Social Change - Kortesoja, Matti (Springer Nature, 2023)
This open access book is the first book that attempts to treat the notion of articulation as an important concept to be added to the lexicon of communication studies and social science. It constitutes the first comprehensive and systematic discussion of 'articulation' in English, providing an introduction of its usages and what has occurred on its 'travels' from one theoretical realm to another in political philosophy, structural linguistics, new economic anthropology, cultural studies and post-Marxist discourse theory. The proposed research takes a relational approach to society and social action in a way that recognises their relative autonomy. It entails an introduction of the 'discursive turn' in the imagery of society and social change, thereby proving that the relational concept of articulation/Gliederung has potential to consider society as both a structured, complex whole and a product of human interaction.